Formation Mechanism and the Height of the Water-Conducting Fractured Zone Induced by Middle Deep Coal Seam Mining in a Sandy Region: A Case Study from the Xiaobaodang Coal Mine. (1st April 2021) - Xie, Xiaoshen; Hou, Enke; Wang, Shuangming; Sun, Xueyang; Hou, Pengfei; Wang, Shibin; Xie, Yongli; Huang, Yongan
Abstract : The height of the water-conducting fractured zone (WCFZ) is a basic parameter related to water protection in coal mines and is also crucial for aquifer protection and mine safety. In order to accurately detect the height and shape and reveal the formation mechanism of the WCFZ, which is caused by middle-deep coal seam mining in a sandy region, the 112201 coalface at the 1# coal mine of Xiaobaodang was taken as a case study. Filed measurements including fluid leakage, borehole TV, and similar simulation were adopted to analyze the regularity of the WCFZ in this area. The detection results of field measurements showed that the maximum height of the WCFZ was 177.07 m in a borehole near the open-off cut, and the ratio of the height of the water-conducting fractured zone divided by the mining thickness was 30.53. The WCFZ acquired an inward-convergent saddle shape, which was inclined to the goaf. The saddle bridge was located at the boundary of the goaf, and the saddle ridge was located at the center of the goaf. Also, through analyzing the results of similar simulations, we found that, in the process of mining, separation cracks and the beam structure were the main forms of overburden disturbance transmitting upward and ahead of mining, respectively. The main cause of the increase in height of the WCFZ was the connection of the separation cracks and vertical cracks caused by fractures of beam structures. The development of the WCFZ was divided into five stages: incubation stage, development stage, rapidly increasing stage, slowly increasing stage, and stable stage. Moreover, the duration of each stage was related to the lithology and mining technology. This research can provide significant theoretical insights for the prediction of the WCFZ, enabling the prevention of water hazards on mine roofs and assisting with water resources protection.